Association Between Diet and Nutrition in the Pathophysiology of Migraine: a Literature Review - Banhatto, Gabriel Machado de Souza Lima; Costa, Hugo Lorran Souza; Nogueira, Guilherme Nobre; Gonçalves, Rafaela Fernandes; Aragão, Gislei Frota (Headache Medicine, 2023)
Full abstract in PDF.